Pengaruh Karakteristik Influencer Pada Keputusan Beli Berdasarkan Model Adopsi Informasi - Triwibowo, Renaldi; Astuti, Budi (Universitas Hamzanwadi, 2024)
This study aims to examine the impact of influencer characteristics, specifically attractiveness, trustworthiness, expertise, and popularity on purchasing decisions for Scarlett beauty products. The research employs a quantitative approach by distributing questionnaires online to 214 respondents who are familiar with the Scarlett brand and know JKT48 as a celebrity. The collected data were analyzed using SmartPLS software with the PLS-SEM method. Based on the result, it is known that attractiveness and trustworthiness have a significant effect on purchase intention. However, expertise and popularity do not significantly influence purchase intention. This study also reveals that purchase intention significantly affects purchasing decisions